Tajdīd al-Tarbīyah al-Islāmīyah ‘inda al-Shaykh al-Ḥājj Imam Zarkasyi - As'ad, Mahrus (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
This paper will investigate the essence of Imam Zarkasyi’s educational reform and its contribution to the development of globally orientated Indonesian madrasah. Based on a descriptive analytical approach, this investigation concludes that Zarkasyi’s educational reform refers to a radical and holistic change that combines modernity and tradition to emphasize not only methodological and institutional aspects but also the importance of the reformulation of the substantial and philosophical bases on which Islamic education should operate. His selective adoption of modern teaching and learning principles, resting firmly on the legacies of the indigenous and classical ‘ulamā’ in a boarding madrasah system, constitutes a cultural achievement that makes an important contribution to the development of modern Islamic science education and theory. Also, it makes a contribution in developing qualified madrasah suitable for providing education with an ‘Islamic character’ without ignoring the students’ academic needs in facing global challenges.DOI: 10.15408/sdi.v22i2.1922